SIMULASI AKTIVITAS KESTABILAN INTI PELURUHAN DERET NEPTUNIUM DENGAN PENDEKATAN ENERGI IKAT INTI MODEL TETES CAIRAN - Auralia Febriandina; Trapsilo Prihandono; Albertus Djoko Lesmono (JURNAL PEMBELAJARAN FISIKA, 2022)
The purpose of this study was to calculate the activity, binding energy, and disintegration energy produced by the decay of radioactive substances in the Neptunium series based on the liquid drop core model. The research steps: 1) prepare supporting data for research on activity and binding energy on nuclear stability decay; 2) review the material that has been obtained; 3) perform calculation simulations; 4) analyze and discuss the calculation results; 5) conclude the research results. The conclusion in this study is that the activity value has increased linearly with a range of values ​​from Bq to Bq. The binding energy decreased linearly with values ​​ranging from 1797.4088 MeV to 1627.7112 MeV. Meanwhile, the binding energy of the nucleons increases linearly. The disintegration energy in the Neptunium series has the largest positive value (Q>0) of 5.2712 MeV and the smallest disintegration energy of Radium-225 which is -0.4317 MeV. Keyword : The activity, binding energy, liquid drop model